Application of Automatic Salt Packaging Technology to Increase Salt Production in the Minamas Pansela KUGAR Group Industry in Glempangpasir Village, Adipala District - Ria Manurung; Agus Suparno; Anastasia Febiyani (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Glempangpasir Village, Adipala District, Cilacap Regency, Central Java Province, is one of the local scale salt production centers. Salt farmers in this village apply the Tunnel system, which is the process of making salt in a closed way starting from the natural water process from the sea to old water, which ends at the crystallization table. This system is proven to produce better quality, white, and cleaner salt. The problem is that the salt packaging process is still manual with simple plastic adhesive sealer equipment. The tool's small size requires several people's labor because it must be put into plastic, weighed, and clamped with simple equipment. The workforce required is usually three people or at least two people so that the work can complete the job correctly. It takes a long time because everything is manual, and the wrapper often leaks because the results of adhesive clamps are not strong or not tight. This PKM activity speeds up the salt packaging process, increases the number of salt processing results due to automatic machines, and increases the tidiness of salt production because it can glue plastic, so it doesn't penetrate the air. Modern automatic salt packaging machines are built with functions that can help the GUKAR group to produce more salt production through the speed of the packaging machine so that the salt production output will increase 100% in terms of production quantity.